MiRNAs are now starring in "No Time to Die: Overcoming the chemoresistance in cancer". Issue 3 (9th June 2022) - Bhatia, Anmol; Upadhyay, Atul Kumar; Sharma, Siddharth
Abstract: Cancer is a leading cause of death globally, with about 19.3 million new cases reported each year. Current therapies for cancer management include—chemotherapy, radiotherapy, and surgery. However, they are loaded with side effects and tend to cause toxicity in the patient's body posttreatment, ultimately hindering the response towards the treatment building up resistance. This is where noncoding RNAs such as miRNAs help provide us with a helping hand for taming the chemoresistance and providing potential holistic cancer management. MicroRNAs are promising targets for anticancer therapy as they perform critical regulatory roles in various signaling cascades related to cell proliferation, apoptosis, migration, and invasion. Combining miRNAs and anticancer drugs and devising a combination therapy has managed cancer well in various independent studies. This review aims to provide insights into how miRNAs play a mechanistic role in cancer development and progression and regulate drug resistance in various types of cancers. Furthermore, next‐generation novel therapies using miRNAs in combination with anticancer treatments in multiple cancers have been put forth and how they improve the efficacy of the treatments. Exemplary studies currently in the preclinical and clinical models have been summarized. Ultimately, we briefly talk through the challenges that come forward with it and minimize them.